Chromatoid body: Remnants of nucleolar proteins during spermatogenesis in triatomine (Heteroptera, Triatominae) - Silistino-Souza, Rosana [UNESP]; Peruquetti, Rita Luiza; Taboga, Sebastiao Roberto [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
In this study, we analyzed fibrillarin nucleolar protein expression in CBs of spermatogenic cells from testicular follicles of Triatoma sordida and Triatoma infestans. In the structural and ultrastructural analysis, it was used impregnation by silver ions, immunocytochemistry, immunofluorescence and transmission electron microscopy using antibodies against fibrillarin. Regarding the results, the fibrillarin nucleolar protein marked the nucleus and some cytoplasmic spots of germ cells during spermatogenesis in triatomines. These data suggest that fibrillarin could be a constituent of the CB that was most likely derived from nucleolar fragmentation. This is the first time that fibrillarin protein expression has been shown in the CB during spermatogenesis progression in triatomines. The knowledge regarding CB constituents may help to expand the understanding of the physiological role of this structure and the role that it plays in the reproductive biology of triatomines, which are vectors of Chagas Disease. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Chromatoid body; Triatoma sordida; Triatoma infestans; Fibrillarin nucleolar protein; Spermatogenesis